Pengaruh Pendapatan Asli Daerah Dan Belanja Modal Terhadap Tingkat Kemandirian Keuangan Daerah Dengan Pertumbuhan Ekonomi Sebagai Variabel Moderating - Tri Utari Handayani; Erinos NR (Universitas Negeri Padang, 2020)
This study aims to examine the effect of regional original income and capital expenditure on regional financial independence with economic growth as a moderating variable. The sample used in this study is the district / city of West Sumatra Province with a sampling method that is total sampling, so that a sample of 12 districts and 7 cities in West Sumatra is obtained. This study uses multiple regression data analysis techniques and residual tests for moderating tests. The results showed that the original regional income had a significant positive effect on regional financial independence, although the effect was only 8.1%. Capital expenditure does not affect the financial independence of the region and economic growth cannot moderate the relationship between the region's original income and capital expenditure to the financial independence of the region.